Easy access : - Keene, Michael L. (McGraw-Hill, 2002)
Easy Access is the only handbook organized by the types of help student writers need. Part One (red tabs) provides a guide to writing processes and products. Solutions to common writing problems and ESL troublespots are found in Part Two (blue tab). Part Three (yellow tab) offers alphabetically organized definitions and examples of grammar, mechanics, and punctuation terms.